Does CO2 Oxidize Ni Catalysts? A Quick X-ray Absorption Spectroscopy Answer - De Coster, Valentijn; Srinath, Nadadur Veeraraghavan; Yazdani, Parviz; Poelman, Hilde; Galvita, Vladimir V (The journal of physical chemistry letters, 2022)
MgAl2O4-supported Ni materials are highly active and cost-effective CO2 conversion catalysts, yet their oxidation by CO2 remains dubious. Herein, NiO/MgAl2O4, prepared via colloidal synthesis (10 wt % Ni) to limit size distribution, or wet impregnation (5, 10, 20, and 40 wt % Ni), and bare, i.e., unsupported, NiO are examined in H2 reduction and CO2 oxidation, using thermal conductivity detector-based measurements and in situ quick X-ray absorption spectroscopy, analyzed via multivariate curve resolution-alternating least-squares. Ni reoxidation does not occur for bare Ni but is observed solely on supported materials. Only samples with the smallest particle sizes get fully reoxidized. The Ni-MgAl2O4 interface, exhibiting metal-support interactions, activates CO2 and channels oxygen into the reduced lattice. Oxygen diffuses inward, away from the interface, oxidizing Ni entirely or partially, depending on the particle size in the applied oxidation time frame. This work provides evidence for Ni oxidation by CO2 and explores the conditions of its occurrence and the importance of metal-support effects.MgAl2O4-supported Ni materials are highly active and cost-effective CO2 conversion catalysts, yet their oxidation by CO2 remains dubious. Herein, NiO/MgAl2O4, prepared via colloidal synthesis (10 wt % Ni) to limit size distribution, or wet impregnation (5, 10, 20, and 40 wt % Ni), and bare, i.e., unsupported, NiO are examined in H2 reduction and CO2 oxidation, using thermal conductivity detector-based measurements and in situ quick X-ray absorption spectroscopy, analyzed via multivariate curve resolution-alternating least-squares. Ni reoxidation does not occur for bare Ni but is observed solely on supported materials. Only samples with the smallest particle sizes get fully reoxidized. The Ni-MgAl2O4 interface, exhibiting metal-support interactions, activates CO2 and channels oxygen into the reduced lattice. Oxygen diffuses inward, away from the interface, oxidizing Ni entirely or partially, depending on the particle size in the applied oxidation time frame. This work provides evidence for Ni oxidation by CO2 and explores the conditions of its occurrence and the importance of metal-support effects.